Cocultivation Study of Monascus spp. and Aspergillus niger Inspired From Black-Skin-Red-Koji by a Double-Sided Petri Dish - Yuan, Xi; Chen, Fusheng (Frontiers in Microbiology, 2021)
Cocultivation is an emerging and potential way to investigate microbial interaction in the laboratory. Extensive researches has been carried out over the years, but some microorganism cocultivation are not easy to implement in the laboratory, especially the fungus-fungus (FF) cocultivation, owing to the obstacles such as fungal different growth rate, limited growing space, hyphae intertwining, and difficulty of sample separation, etc. In this research, a double-sided petri dish (DSPD) was designed and carried out as a tool to study FF cocultivation in the laboratory. A natural FF cocultivation of Monascus spp. and Aspergillus niger inspired from black-skin-red-koji (BSRK), were studied. By using DSPD, the aforementioned obstacles in the FF cocultivation study were overcome through co-culturing Monascus spp. and A. niger on each side of DSPD. The characteristics of monocultured and co-cultured Monascus spp. and A. niger were compared and analyzed, including colonial and microscopic morphologies, and main secondary metabolites (SMs) of Monascus spp. analyzed by high performance liquid chromatography. And a novel SM was found to be produced by Monascus ruber M7 when co-cultured with A. niger CBS 513.88. Since the above mentioned obstacles, were overcome, we obtained good quality of transcriptome data for further analysis. These results indicate that DSPD might be an efficient tool for investigation of microbial interaction, in particular, for FF interaction.